Design of Pineapple Peeler with Manual Press System - Nando Edi Pramono Lingga; Achwil Putra Munir; Nazif Ichwan (Universitas Sumatera Utara, 2014)
The handling of pineapple after harvest in skin peeling on farmer level generally are done manually by knife. Therefore, to overcome this weaknesses and disadvantages, a semi mechanic pineapple skin peeler was design that could peels the pineapple skin faster than manually, so it could made the work capacity increased, more neat peeling results, reducing the labor and can be used by anyone. The research was done by study of literature and observing the pineapple skin peeler with press manual system. Then designing the shape and coupling the components of the pineapple skin peeler. The pineapple skin peeler capacity for 11 cm, 10 cm and 7,5 cm blades diametre before honed were 139,76; 143,26; 149,25 pineapples per hour respectively. The pineapple skin peeler capacity for 11 cm, 10 cm, 7,5 cm blade diametre after honed were 143,47; 144,57; and 150,76 pineapples per hour respectively. Keywords : Blade, equipment design, pineapple skin peeler